To teach, to delight, and to move: theological education in a post-Christian world - Cunningham, David S. (Cascade Books, 2004)
Foreword / L. Gregory Jones -- Introduction: Re-visioning theological education -- The classical rhetorical tradition and theological education / David S. Cunningham, Don H. Compier, and James L. Boyce -- Beyond the classical paradigm : contemporary rhetorical analysis and theological education / Janet L. Weathers -- Rhetoric, postmodernism, and theological education : what has Vincennes to do with Athens or Jerusalem? / A.K.M. Adam -- Theology as communication : revelation, faith, and the church as ongoing dialogues / Bradford E. Hinze -- Theology as confession : redeeming a theological trope for pedagogy / Stephen H. Webb -- Theology as discernment : truth, power, and authority / Wes Avram -- Theology as testimony : rhetoric, public theology, and education for ministry / Don H. Compier -- Rhetoric and practical theology : toward a new paradigm / Richard R. Osmer -- Rhetoric and the word of God : treasure in earthen vessels / James L. Boyce -- Rhetoric and historical theology : Gregory the Theologian / Frederick W. Norris -- Rhetoric and Christian doctrine : trinity and teaching / David S. Cunningham -- Rhetoric and proclamation : a relational paradigm / Susan Karen Hedahl -- A rhetorical approach to theological education : assessing an attempt at re-visioning a curriculum / Donald Juel and Patrick Keifert